Investigations into advanced concepts of terminal and base-station antennas. - Kabacik, Pawel
The development of essentially new terminal and base-station antennas has become one of the most important tasks in contemporary antenna engineering. Improvements in antenna technology must be accomplished regardless of progress in signal processing. Comprehensive research on such antennas has been carried on at the Wroclaw University of Technology, Poland, for several years now. There are three major fields of interest: small antennas, base-station antennas, and smart-antenna technology. The small antennas investigated-either planar or conformal-approach the physical limits of allowable dimensions. They operate with a number of systems that might involve advanced signal-processing techniques. The scope of the research also includes studies on the interactions between terminal antennas and humans.
Keywords: Land mobile radio cellular systems; Land mobile radio equipment; Mobile antennas; Multibeam antennas; Multifrequency antennas; Signal processing antennas; Conformal antennas; Cylindrical arrays; Handset antennas; Smart antennas